A Comparative Study of Dermatoglyphic Patterns of Fingers in Normal Children and In Children with Congenital Heart Diseases - Shivaleela C; Nandyal V B; Lakshmiprabha S; Kumar G V (Academia Anatomica International, 2019)
Introduction: Dermatoglyphics is the study of epidermal ridges and their configurations on the palmar and the plantar regions. Currently dermatoglyphics is being used as a tool in the field of biology, anthropology, genetics and medicine to explain, compare and to predict the occurrence of bio medical events. Finger prints are usually categorized into three basic groups namely arches (60-65%), loops (30-35%) and whorls (5%). Any prenatal insult during this critical period of embryogenesis/organ system development should have an influence on the dermatoglyphic patterns.4Congenital heart defects are a heterogeneous group of diseases in which etiology, importance of genetic as well as environmental factors have been recognized. These defects show a familial tendency but no Mendelian pattern of inheritance has been described. In the present study, finger dermatoglyphic patterns in congenital heart diseases are studied and compared with controls. Subjects and methods: Dermatoglyphics are studied in 100 children with congenital heart diseases, both males and females. The dermatoglyphic patterns of palms and fingers were studied and the information was recorded systematically and statistically analyzed. Results: Ventricular septal defects (VSD) form the majority in the both the males (50%) and females (34.8%) in the congenital heart diseases group, followed by Atrial septal defects (ASD) in both males (20.4%) and females (39.1%). In both, the cases and controls group, it is found that the majority are loops followed by whorls and then the arches. The increase in whorls in congenital heart diseases is statistically significant with p value < 0.001. Comparing the cases with controls it is found that the Whorls (p < 0.001) and the loops (p <0.001) were statistically significant, it means that the Whorls are more frequently found in congenital heart diseases than the controls. Conclusion: Congenital heart diseases are associated with abnormal dermatoglyphic patterns. Increased number of Whorls and decreased number of Arches are seen in the congenital heart disease children. The above fingerprint pattren may help as a diagnostic aid in diagnosis of congenital heart diseases in children. They may also help in distinguishing congenital heart diseases from the functional and acquired heart diseases. A larger sample study is required to ascertain the value of this dermatoglyphic parameter as a diagnostic tool in congenital heart diseases in children.